Prevalence of potentially inappropriate prescribing in older people in primary care and its association with hospital admission: longitudinal study. (14th November 2018) - Pérez, Teresa; Moriarty, Frank; Wallace, Emma; McDowell, Ronald; Redmond, Patrick; Fahey, Tom
Abstract: Objective: To determine whether hospital admission is associated with potentially inappropriate prescribing among older primary care patients (aged ≥65 years) and whether such prescribing was more likely after hospital admission than before. Design: Longitudinal study of retrospectively extracted data from general practice records. Setting: 44 general practices in Ireland in 2012-15. Participants: Adults aged 65 years or over attending participating practices. Exposure: Admission to hospital (any hospital admission versus none, and post-admission versus pre-admission). Main outcome measures: Prevalence of potentially inappropriate prescribing assessed using 45 criteria from the Screening Tool for Older Persons' Prescription (STOPP) version 2, analysed both as rate of distinct potentially inappropriate prescribing criteria met (stratified Cox regression) and binary presence of potentially inappropriate prescribing (logistic regression) and adjusted for patients' characteristics. A sensitivity analysis used matching with propensity scores based on patients' characteristics and diagnoses. Results: Overall 38 229 patients were included, and during 2012 the mean age was 76.8 (SD 8.2) years and 43% (13 212) were male. Each year, 10.4-15.0% (3015/29 077 in 2015 to 4537/30 231 in 2014) of patients had at least one hospital admission. The overall prevalence of potentially inappropriate prescribing ranged from 45.3% (13 940/30 789) of patients in 2012 to 51.0% (14 823/29 077) in 2015. Independently of age, sex, number of prescription items, comorbidity, and health cover, hospital admission was associated with a higher rate of distinct potentially inappropriate prescribing criteria met; the adjusted hazard ratio for hospital admission was 1.24 (95% confidence interval 1.20 to 1.28). Among participants who were admitted to hospital, the likelihood of potentially inappropriate prescribing after admission was higher than before admission, independent of patients' characteristics; the adjusted odds ratio for after hospital admission was 1.72 (1.63 to 1.84). Analysis of propensity score matched pairs showed a slight reduction in the hazard ratio for hospital admission to 1.22 (1.18 to 1.25). Conclusion: Hospital admission was independently associated with potentially inappropriate prescribing. It is important to determine how hospital admission may affect appropriateness of prescribing for older people and how potential adverse consequences of admission can be minimised.